Cortical properties of adults with autism spectrum disorder and an IQ>100. (30th September 2018) - Maier, Simon; Tebartz van Elst, Ludger; Perlov, Evgeniy; Düppers, Ansgard Lena; Nickel, Kathrin; Fangmeier, Thomas; Endres, Dominique; Riedel, Andreas
Highlights: Focus on individuals with high-functioning Autism Spectrum Disorder. Decreased gyrification and sulcus depth in autism-related brain regions. The effects did not survive correction for multiple testing. Cortical anomalies in ASD are either weak or only apply to ASD-subgroups. Abstract: Previous studies on cortical volume and thickness measures in autism spectrum disorders (ASD) show inconsistent results. We acquired structural magnetic resonance images of 30 individuals with ASD and individually matched controls and extracted surface-based and deformation-based morphometry measures. All participants had an IQ>100. Neither surface-based cortical thickness nor deformation based gyrification measures differed significantly across groups. Significant decreases but no increases of the gyrification index and sulcus depth could only be observed in the ASD group before correcting for multiple comparisons. This finding suggests that possible cortical anomalies in ASD are either weak or, given the heterogeneity of findings in earlier studies, might only apply to small ASD-subgroups.